A Study on Awareness and Satisfaction towards Employee Welfare Measures - S. Jayanthi; Dr. K. Ilangovan (International Journal of Engineering and Management Research, 2019)
The employees are considered as major resources of all organisations including service as well as manufacturing industries. So in the present day of business world, the companies are giving more benefits to their employees and maintaining good standard measures to make them satisfy in the organisation. The present study is on the above subject which studies the welfare measures. Therefore the reason of the study is to find out how welfare measure are provided by the private organisation and how the employees are satisfied with the company accommodation given to the employees which plays a very important role in the employee satisfaction and their life in the organization. The study found that the employee welfare measures are highly satisfactory in their concern which was done through perfect analysis & interpretation. This study would be helpful for the company and also to improve some welfare and safety activities inside the company.